An internship report and comparative study of educational psychologists' practices pertaining to attention deficit hyperactivity disorder in St. John's, Newfoundland and Harlow, Essex - Hickey, Colleen, 1967- (1998)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1999. Education Bibliography: leaves 61-65. This report outlines an 11-week internship program completed in Harlow, England to comply with regulations set out for the degree of Masters of Education in Educational Psychology. The internship route was chosen by this intern because unique insights are gained and practical training is received through an on-site placement. This report is comprised of three chapters discussing this intern's placement and goals/objectives including rationale, implementation, and evaluation of same. In addition, a comprehensive literature review and an in-depth study of educational psychologists' practices as they pertain to Attention Deficit Hyperactivity Disorder is provided. A semi-structured interview schedule was utilized with four practising educational psychologists in St. John's, Newfoundland and four practising educational psychologists in Essex, England. Responses formed the basis for a comparative analysis. Results indicate that the referral and assessment of ADHD is seen to be ad hoc in both areas. Although the education systems are structured differently, the referral processes lack both structure and procedure. Results also indicate that Newfoundland psychologists rely heavily on standardized assessment tools while British psychologists place more importance on the child's environment. No individual interviewee reported completing a comprehensive battery for the assessment of ADHD. The diagnosis of ADHD is seen as the domain of the medical doctor in both Newfoundland and England. Educational psychologists in both areas feel they should have a greater input into the diagnosis. This non-collaboration between health, education and psychology is a great concern to educational psychologists in both areas. The creation of a multidisciplinary team and more education are seen as answers for a complete and thorough evaluation of the child and his/her environment.